2021
DOI: 10.4081/mrm.2021.777
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors correlated with hypertension secondary from obstructive sleep apnea

Abstract: Background: In 2003, the JNC 7 reported obstructive sleep apnea (OSA) as a cause of secondary hypertension. The prevalence of OSA in hypertension ranges from 30-80%. There are limited data on the prevalence and risk factors of OSA in hypertensive patients. This study thus aimed to evaluate prevalence and clinical predictors of obstructive sleep apnea (OSA) in these patients.Methods: This was a cross-sectional study and conducted at the hypertension clinic at Khon Kaen University’s Srinagarind Hospital, Thailan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 34 publications
2
22
1
Order By: Relevance
“…Third, the outcomes were evaluated only at discharge and not over a longer term. Fourth, some factors possibly related to both stroke and atrial fibrillation were not examined such as laboratory tests and obstructive sleep apnea (25)(26)(27)(28)(29)(30)(31)(32)(33). Finally, authorization to access the database was only for the mentioned study period (2015-2017).…”
Section: Discussionmentioning
confidence: 99%
“…Third, the outcomes were evaluated only at discharge and not over a longer term. Fourth, some factors possibly related to both stroke and atrial fibrillation were not examined such as laboratory tests and obstructive sleep apnea (25)(26)(27)(28)(29)(30)(31)(32)(33). Finally, authorization to access the database was only for the mentioned study period (2015-2017).…”
Section: Discussionmentioning
confidence: 99%
“…The authors also found that obesity was not related to severity of OSA in older adults. Previous studies also showed that obesity may not be related to OSA diagnosis particularly in the elderly and those with hypertension ( 52 , 61 ). Xia et al conducted a retrospective study to show that both low oxygenation and arousal during apneic events in patients with OSA were significantly related to high diastolic blood pressure and hypertension.…”
Section: Summation Of Research Topicmentioning
confidence: 92%
“…This Research Topic focused on clinical aspects of cardiovascular diseases including review, epidemiological, treatment-related, or interventional studies. Cardiovascular consequences of OSA included hypertension, coronary artery disease, cardiac arrhythmia, left ventricular hypertrophy, cardiac failure, and stroke ( 52 60 ).…”
Section: Summation Of Research Topicmentioning
confidence: 99%
“…A report from UK found that 21.3% of 1,275,174 adult patients had one of the cardiovascular diseases [1]. Dyslipidemia is one of the major risk factors for cardiovascular diseases as well as other risk factors such as hypertension or sleep apnea [2], [3], [4], [5]. The previous reports and guidelines recommended lowering low-density lipoprotein cholesterol (LDL-c) in both primary and secondary prevention [6], [7].…”
Section: Introductionmentioning
confidence: 99%